Multifactorial Neonatal Thrombosis in Inferior Vena Cava Dislodged to the Right Atrium: A Case Report - Ziba Mosayebi; Mohammadreza Mirzaaghayan; Reza Shabanian; Behdad Gharib; Elahe Movahedi; minoo dadkhah; Reihaneh Mohsenipour; Maryam Saeedi (Mashhad University of Medical Sciences, 2020)
Background: Neonatal thrombotic diseases can cause mortality or serious morbidity and disability. Case report: In this report, we present a case of neonatal inferior vena cava thromboembolism with several underlying factors. Hereditary thrombophilia and genetic mutation in plasminogen activator inhibitor-1 and MTHFR A1298C genes in conjunction with cleft palate resulted in poor lactation and hypernatremic dehydration. A peripherally inserted central catheter in the inferior vena cava was an additional underlying factor. Thrombosis mass was dislodged to the right atrium while asymptomatic and accidentally detected during routine echocardiography. Conclusion: Surgical thrombectomy was done successfully, and the mass was removed from the right atrium.